RANCANG BANGUN SISTEM ONLINE PUSKESMAS BERBASIS WEB DENGAN MENGGUNAKAN EXTREME PROGRAMMING PADA PUSKESMAS PAGEDANGAN - Irpan Andika Saputra; Niki Ratama (Journal of Research and Publication Innovation, 2025)
The online registration system for community health centers is a manual registration system that does not yet have a computerized system. This research aims to build a fast, accurate, efficient system using a web-based online system. The research method used is a qualitative research method with data collection methods, namely observation, interviews and literature study. The system method used for analysis and design is using an Entity Relationship Diagram (ERD). The programming language used is Hypertext Preprocessor (PHP) and the database uses MySQL and this website was created using the Extreme programming method so that each process produces a system that can be developed according to what is desired, making it easier for admins to manage master data and citizen registration so that with It is also hoped that the development of this system will make it easier for people to register themselves at the health center and also search for information at the health center. This system is also made so that it is easy to use, therefore this system is very efficient and not long-winded, it also aims to make people happy when using it.